Acquisition of electronic information resources: a bibliometric study (2019-2023) (Bibliouniversitas@ABRM.md, 2025)
This paper presents data on informational resources available in the Institutional Electronic Archives, Open Research Archive USARB and the Digital Library. It highlights the library's experience in recording electronic resources.
Keywords: digital library; IR ORA USARB; electronic resources